1995
DOI: 10.1101/gad.9.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a TFIIIC2 subunit (TFIIIC beta) whose presence correlates with activation of RNA polymerase III-mediated transcription by adenovirus E1A expression and serum factors.

Abstract: TFIIIC2 is a general factor essential for transcription of 5S RNA, tRNA, and VA RNA genes by mammalian RNA polymerase III and consists of two forms designated THIIC2a and TFIIIC2b. TFIIIC2a and TFIIIC2b share common subunits of 220, 102, 90, and 63 kD but differ with respect to transcription activity and the presence of a presumptive 110-kD subunit in the active form (TFIIIC2a). Because both forms can bind the promoter directly, a selective role for the 110-kD subunit in the regulation of RNA polymerase III ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
1
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 51 publications
(76 reference statements)
4
102
1
2
Order By: Relevance
“…Furthermore, adenoviral infection can selectively increase the level of TFIIIC110 (Sinn et al, 1995). This led us to wonder if TFIIIC2 might also be induced when cells are infected and transformed by HPV, but we found no evidence that this is the case.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, adenoviral infection can selectively increase the level of TFIIIC110 (Sinn et al, 1995). This led us to wonder if TFIIIC2 might also be induced when cells are infected and transformed by HPV, but we found no evidence that this is the case.…”
Section: Discussioncontrasting
confidence: 52%
“…) also indicate that human TFIIIB contains a third subunit with weak sequence relationships to the third (largest) subunit of yeast TFIIIB. Human TFIIIC1, which has no known counterpart in yeast, is less well characterized but stabilizes and extends promoter interactions of TFIIIC2 (for review, see Wang and Roeder 1996) and can interact with TFIIIC2 both in the absence and presence of promoter DNA (Sinn et al 1995;Z. Wang, and R.G.…”
Section: A Novel Accessory Factor For Initiation By Rna Pol IIImentioning
confidence: 99%
“…Studies of these factors in various regulatory responses have shown that serum factors and early stage adenovirus infection stimulate RNA Pol III transcription by increasing the levels of the active form of TFIIIC2 (Sinn et al 1995), whereas transcription has been reported to be down-regulated through TFIIIB in differentiating mouse F9 embryonic carcinoma (EC) cells and during mitosis (Scott et al 1983;White et al 1989;Gottesfeld et al 1994). Transcription by RNA Pol III is also down-regulated in other situations, including growth into stationary phase (Tower and Sollner-Webb 1988), growth arrest induced by protein synthesis inhibitors (Gokal et al 1986), starvation for an essential nutrient (Hoeffler and Roeder 1985), and late-stage virus infection (Sö derlund et al 1976;Weinmann 1976).…”
mentioning
confidence: 99%
“…This inhibition may be reversed by viruses such as SV40, Hepatitis B virus and human T cell leukemia virus type 1 (White, 1998). SV40 large T Antigen, as well as serum stimulation or adenovirus infection, increase the amount of the 110 kDa subunit of TFIIIC2, thereby activating the factor and, accordingly, PolIII transcription (Sinn et al, 1995;Damania et al, 1998;Larminie et al, 1999). All TFIIIC2 subunits are overexpressed in ovarian tumours, a leading cause of gynecological cancer deaths in the USA (Winter et al, 2000).…”
mentioning
confidence: 99%